Environmental factors determining the survival of winter ticks (Dermacentor albipictus) at different life stages in Québec, Canada - Morgane Le Goff; Christian Dussault; Julien H. Richard; Steeve D. Côté (Ticks and Tick-Borne Diseases, 2025)
Ticks are responsible for large economic losses because of their impact on livestock and wildlife. In recent years, winter ticks (Dermacentor albipictus) have caused mass mortalities in moose (alces) populations of North America, leading to host mortality due to severe blood loss. During their off-host stages (i.e. egg and larvae), winter ticks are particularly vulnerable to mortality because of potential exposure to stressful abiotic conditions that could dehydrate eggs or freeze larvae. We conducted a field experiment in Québec, Canada, to better understand larval questing behaviour and assess the ability of unfed larvae to survive over the winter to the following fall. In the laboratory, we tested the tolerance of eggs to different saturation deficits reflected by combinations of temperature and humidity and evaluated the tolerance of larvae to sub-freezing temperatures. We found that unfed winter tick larvae did not survive until a second fall regardless of habitat types (open, closed or sheltered from the snow) and thus could not quest for a host for two consecutive years. However, unfed larvae withstood short-term exposure to low sub-freezing temperatures, potentially prolonging their questing period and increasing the likelihood of moose infestations. Egg survival varied among saturation deficits, but survival tended to be higher at 30 °C and lower at 22 °C regardless of the saturation deficit. Overall, we found that the free stages of winter ticks are highly tolerant of extreme conditions, reinforcing the concern that winter ticks represent for moose populations.